A Review of Impact of Tobacco Use on Patients with Co-occurring Psychiatric Disorders - Arghya Pal; Yatan Pal Singh Balhara (SAGE Publishing, 2016)
Consumption of tobacco has been a worldwide problem over the past few decades due to the highly prevalent tobacco-attributable complications. Tobacco use has also been found to be more prevalent in patients with psychiatric disorders. Therefore, we conducted this review about the impact of tobacco use on co-occurring psychiatric disorders. Various facets of this interaction between tobacco use among those with co-occurring psychiatric disorders have been explored. It has been found that people with psychiatric disorders have a higher chance of currently smoking tobacco and lesser chance of cessation. Tobacco use and mental disorders continue to share a complex relationship that has been further evolving after the change in the pattern of tobacco use and also the advent of newer modalities of treatment. However, at the same time, it is believed that cessation of smoking may lead to improvement in the symptoms of mental illness.